Parents' Strategy in Developing Early Childhood Creativity During the Covid-19 Pandemic - Aslindah, Andi (Educationist: Journal of Educational and Cultural Studies, 2023)
This research is motivated by the importance of developing creativity in early childhood anywhere, anytime, and under any conditions. The Covid-19 pandemic is not an obstacle to being productive and creative. Precisely because more activities are carried out at home, a lot of time can be used to be closer to family. The role of the family is inseparable in helping the development and growth of children, including in helping children develop creativity. The purpose of this study was to find out parents' strategies in developing early childhood creativity during the Covid-19 pandemic. This study uses a qualitative method with a qualitative descriptive approach. Data collection was carried out through interviews with 5 research subjects, parents who had early childhood as respondents. To check the validity of the data, triangulation techniques are used so that the research data obtained can be scientifically justified. The steps in the analysis of research data are reduction, presentation of data, then drawing conclusions in response to the formulation of the problem. The results of this study indicate that parents play a role in developing children's creativity during the co-19 pandemic. Several strategies were carried out by parents so that the development of children's creativity would continue to develop during a pandemic as it is today, such as building children's self-confidence through an attitude of acceptance and respect for children, providing opportunities for children to express and explore, providing sufficient time and space for playing and doing assignments, observing and supporting activities that children are interested in, establishing good cooperation with children, creating a pleasant home environment, and facilitating media (means) that can support the development of children's creative potential.